Intersemiotische Kommunikation im frühen Fremdsprachenunterricht - Gorąca, Gabriela (Glottodidactica, 2008)
The article refers to the constitutive elements of intersemiotic communication in the didactics of foreign languages. It indicates, that you can communicate not only using verbal language, but nonverbal elements such as for example pictures or music influencing the sense of an utterance, as well. Language and semiotic elements of communication refer to human feelings and are often interconnected. Constellation of them simplifies learning of foreign languages especially by small children. It's important therefore to get to know glottodidactical techniques using music and picture to increase effectiveness of language acquisition.